Diagnostic Test of Serum Pregnancy-Associated Plasma Protein-A Level as Biomarker for Early Diagnosis of Acute Myocardial Infarction - Novida Dwi Astuti; JB. Suparyatmo; Amiroh Kurniati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Acute coronary syndrome is the primary cause of death from heart disease worldwide. This syndrome is caused by ruptured/eroded coronary atherosclerotic plaque, resulting in partial/total occlusion of thrombosis. It is necessary to find novel cardiac biomarkers for the identification of plaque progression before ischemic and myocardial necrosis events. Pregnancy Associated Plasma Protein-A (PAPP-A) is an atherosclerotic mediator proven to be a biomarker for plaque instability. This study aimed to determine the performance of serum PAPP-A as a biomarker for the early diagnosis of AMI. This research was an analytical observational study with a cross-sectional approach. Serum PAPP-A was measured using enzyme-linked immunosorbent assay in 82 new patients. They had ACS and were admitted to the emergency installation of Dr. Moewardi Hospital in Surakarta in August-September 2019. The subjects were grouped into the AMI group (NSTEMI and STEMI) consisting of 49(59.8%) subjects and non-AMI (UAP) group composed of 33(40.2%) subjects based on ACS diagnostic criteria of PERKI 2018. Receiver Operator Characteristic (ROC) curve analysis showed that PAPP-A was a good discriminator between AMI and non-AMI patients. The area under the curve was 0.968, 95% CI (0.932–1.004), with a sensitivity of 91.8% and specificity of 90.9% (p< 0.05). The cut-off value from the ROC curve was 2,526 ng/mL. Serum PAPP-A level has excellent performance as a biomarker for early diagnosis of AMI. It can also function as a screening instrument for the identification of UAP cases developing into AMI.